2018
DOI: 10.5539/mas.v12n11p181
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Closed Price Time Series Data Using ARIMA Model

Abstract: Closed price forecasting plays a main rule in finance and economics which has encouraged the researchers to introduce a fit model in forecasting accuracy. The autoregressive integrated moving average (ARIMA) model has developed and implemented in many applications. Therefore, in this article the researchers utilize ARIMA model in predicting the closed time series data which have been collected from Amman Stock Exchange (ASE) from Jan. 2010 to Jan. 2018. As a result this article shows that the ARIMA model has s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 17 publications
0
27
0
3
Order By: Relevance
“…On the other hand, to apply ARIMA statistical technique, there are many constraints such as making data stationary or linearizing by taking the exponential of data. In addition, this method is generally poor at predicting turning points (Meyler, Kenny, & Quinn, 1998) (Wadi, 2018) which happens in our case.…”
Section: Theoretical Background Of the Algorithmsmentioning
confidence: 67%
“…On the other hand, to apply ARIMA statistical technique, there are many constraints such as making data stationary or linearizing by taking the exponential of data. In addition, this method is generally poor at predicting turning points (Meyler, Kenny, & Quinn, 1998) (Wadi, 2018) which happens in our case.…”
Section: Theoretical Background Of the Algorithmsmentioning
confidence: 67%
“…Many well-known times series forecasting methods have been used for this reason. Autoregressive Integrated Moving Average (ARIMA) models have been especially popular in the stock market's time series prediction [17,63]. Furthermore, hybrid methods exploiting similar approaches have also been introduced.…”
Section: Related Workmentioning
confidence: 99%
“…Wadi et al [1] found the best-fit ARIMA model for forecasting the closed price of Jordan's ASE, with p, d, and q parameters of 2, 1, and 1 correspondingly, and RMSE=4 . For the banking stock data of Jordan's ASE, the ARIMA p=1, d=1, and q=2 suited most with RMSE=1.4 Almasarweh and Alwadi [2].…”
Section: Literature Reviewmentioning
confidence: 99%